Kombinasi Pemberian Sereh dan Kunyit terhadap Penurunan Intensitas Nyeri Menstruasi pada Remaja Putri Kelas VII di SMP N 2 Kuta - Marisa, Venny (STIKES ADVAITA MEDIKA TABANAN, 2024)
Intoduction: Adolescence is a transition period marked by physical, emotional and psychological changes.Menstrual discomfort is one of the most frequent illnesses associated with menstruation. Non-pharmacological therapy is used to alleviate menstrual discomfort, specifically a combination of lemongrass and turmeric. The purpose of this study was to assess whether administering lemongrass and turmeric reduced the menstrual pain intensity felt by adolescent girls. Method: This study employed a quasi-experimental research design using a Non-Equivalent Control Group Design and purposive sampling, involving 64 grade VII adolescent girls separated into two groups: the intervention and the control group. Pain intensty was assessed using a VAS (Visual Analog Scale) questionnaire.. Result: The results of This study’s findings obtained that the pretest p-value for the treatment group was 0.000<0.05, indicating a difference in menstrual pain after the intervention. However, the post-test p-value for the control group was 1,000>0.05, indicating no difference in menstrual pain in the control group. Mann Whiteny analysis yielded a p value of 0.00 (<0.05), indicating that the combination of lemongrass and turmeric reduced menstruation pain felt by adolescent girls. Sugestion: It is intended that the combination of lemongrass and turmeric will be considered when delivering complete midwifery care to adolescent girls in order to minimize the menstrual pain intensity.